Catalytic Deoxydehydration of Glycols with Alcohol Reductants. Issue 4 (26th March 2013) - Boucher‐Jacobs, Camille; Nicholas, Kenneth M.
<x xml:space="preserve">Abstract</x> Top shelf dehydration: Ammonium perrhenate catalysts combined with benzylic alcohol reductants are used for the efficient deoxydehydration of glycols to olefins. The olefin and aldehyde products can be easily separated and isolated. It is also demonstrated that the catalyst can be recovered and reused because of its low solubility in aromatic solvents.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>